2001
DOI: 10.1086/321994
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Imprinting and the Origin of Obligate Brood Parasitism in Birds

Abstract: We discuss two pathways along which obligate brood parasitism (OBP) may evolve and examine some of the critical steps that must be passed by letting great tits Parus major be reared by blue tits Parus caeruleus in a field experiment. The cross-fostered chicks survived well in blue tit nests, but their local recruitment and reproductive success was much lower than that of controls. The effect was strongest when great tits grew up with siblings of the host species rather than with conspecific siblings in blue ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…The present results support those of a previous crossfostering experiment with great tits in the same study area, where we found that only a few great tits reared by blue tits paired with a conspeci c bird as a yearling (Slagsvold & Hansen 2001). The cross-fostered birds appeared to be strongly imprinted on the blue tit host, which seemed to explain the low pairing success.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present results support those of a previous crossfostering experiment with great tits in the same study area, where we found that only a few great tits reared by blue tits paired with a conspeci c bird as a yearling (Slagsvold & Hansen 2001). The cross-fostered birds appeared to be strongly imprinted on the blue tit host, which seemed to explain the low pairing success.…”
Section: Discussionsupporting
confidence: 91%
“…Learning from parents during early development may crucially in uence future mate-choice decisions of young birds (ten Cate & Vos 1999) and mammals (Kendrick et al 1998;Penn & Potts 1998). Recently, the importance of this well-known process of sexual imprinting has been recognized in the elds of sexual selection, hybridization, speciation and brood parasitism (Laland 1994;Grant & Grant 1997;Price 1998;Irwin & Price 1999;Owens et al 1999;ten Cate & Vos 1999;Witte et al 2000;Slagsvold & Hansen 2001). In birds, sexual imprinting seems to be the rule rather than the exception (ten Cate & Vos 1999), but little is known about the relative importance of learning and genes in shaping the sexual preferences and how this may vary among species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although brood parasitism imparts fitness benefits through increased reproductive output without the costs associated with parental care, it presents a set of ontogenetic challenges for the developing young compared with parental birds in which sexual imprinting leads to the recognition of conspecifics. One of the earliest developmental challenges faced by juvenile brood parasites is to avoid mis-imprinting on the species of unrelated parents and siblings (Slagsvold and Hansen, 2001). Imprinting on the song or visual cues of the foster parent would result in inaccurate social recognition well into adulthood, which in turn would lead to substantial fitness costs through misdirected reproductive effort.…”
Section: Introductionmentioning
confidence: 99%
“…In the face of costly hybridization, mating with conspecifics generally yields greater fitness, raising the question of how individuals recognize compatible partners for sexual reproduction (Salzen & Cornell 1968). Among birds, parental care is most often provided directly by the genetic parents, such that the phenotypic attributes of attending adults and siblings generally provide reliable information about the speciesspecific traits of suitable mates (Lorenz 1937;Irwin & Price 1999;ten Cate & Vos 1999;Slagsvold & Hansen 2001). In contrast, brush turkeys and their allies (Megapodidae) have no post-hatch parental care and obligate brood parasites are reared by other species Goth & Hauber 2004).…”
Section: Introductionmentioning
confidence: 99%